Use of Statins by Medicare Beneficiaries Post Myocardial Infarction - Mary C. Schroeder PhD; Jennifer G. Robinson MD; Cole G. Chapman PhD; John M. Brooks PhD (SAGE Publishing, 2015)
Even though guidelines strongly recommend that patients receive a statin for secondary prevention after an acute myocardial infarction (MI), many elderly patients do not fill a statin prescription within 30 days of discharge. This paper assesses whether patterns of statin use by Medicare beneficiaries post-discharge may be due to a mix of high-quality and low-quality physicians. Our data come from the Centers for Medicare & Medicaid Services (CMS) Chronic Condition Data Warehouse (CCW) and include 100% of Medicare beneficiaries hospitalized for an acute myocardial infarction in 2008 or 2009. Our study sample included physicians treating at least 10 Medicare fee-for-service beneficiaries during their MI institutional stay. Physician-specific statin fill rates (the proportion of each physician's patients with a statin within 30 days post-discharge) were calculated to assess physician quality. We hypothesized that if the observed statin rates reflected a mix of high-quality and low-quality physicians, then physician-specific statin fill rates should follow a u-shaped or bimodal distribution. In our sample, 62% of patients filled a statin prescription within 30 days of discharge. We found that the distribution of statin fill rates across physicians was normal, with no clear distinctions in physician quality. Physicians, especially cardiologists, with relatively younger and healthier patient populations had higher rates of statin use. Our results suggest that physicians were engaging in patient-centered care, tailoring treatments to patient characteristics.